RISK MANAGEMENT AT THE MICRO WAQF BANK (BWM) BERKAH RIZQI LIRBOYO CITY OF KEDIRI - Wicaksono, Adi; Anggraini, Reni (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Financial inclusion has been a policy focus in Indonesia for the last decade. To improve the financial inclusion index, the President of the Republic of Indonesia with OJK launched the Bank Wakaf Mikro (BWM). So far, 62 BWMs have been established in Indonesia with a total of 62 thousand beneficiaries and total financing of IDR100.6 billion. One that has successfully increased financial inclusion is BWM Berkah Rizqi Lirboyo in Kediri City, which received the 2019 TPAKD Award. BWM Berkah Rizqi Lirboyo uses the Qardh al-hasan contract. Although it is nonprofit, BWM must be able to manage risks or uncertainties. For this reason, there must be a risk management strategy to avoid default. By using a realist ethnographic qualitative approach, this research aims to get an overview of how risk management at BWM Berkah Rizqi Lirboyo is carried out and how the interaction between administrators and borrowers so that NPL are 0%. The findings in the field show that the risk management chosen by BWM Berkah Rizqi Lirboyo is to control risk and transfer financing risk. In addition, it utilizes social capital to reduce information asymmetry.